PENERAPAN MODEL LITERASI SASTRA DALAM KEGIATAN SANGGAR SASTRA BALAI PUSTAKA - Maulida Rachma Herliani; Nuning Kurniasih; Andri Yanto (Universitas Negeri Makassar, 2024)
This research aims to find out the implementation of the literary literacy model at Balai Pustaka Literary Centre. This research uses a qualitative research method with a case study approach. Data collection techniques were conducted through observation, interviews, and literature study, with the research subjects being the founders and members of Sanggar Sastra Balai Pustaka. The data analysis used in this research is qualitative data analysis, which consists of reduction, data presentation, and conclusion. The results show that in its activities, Sanggar Sastra Balai Pustaka has applied the response model, transactional model, green model, and socio-anthropological model. The model is used effectively in teaching literature, which includes the process of creating works and literature appreciation classes. The teaching methods are presented in a unique way that stimulates participants' responses and interest in learning literature. This activity was able to increase the interest in literature for the participants, both during the teaching process and afterwards.